Encyclopaedia of Psychology - Kumar, Arvind; Devi laxmi; Yadav, C. P; Kumar, Arun (New Delhi Anmol Publications, 2002)
Role theory and the human sciences. Constructing psychological services in social services departments.Social services,psychology and psychologists Whose psychology